Confederate Industry : Manufacturers and Quartermasters in the Civil War - Wilson, Harold S., 1935- (Book collections on Project MUSE., 2002)
By 1860 the South ranked high among the developed countries of the world in per capita income and life expectancy and in the number of railroad miles, telegraph lines, and institutions of higher learning. Only the major European powers and the North had more cotton and woolen spindles. This book examines the Confederate military's program to govern this prosperous industrial base by a quartermaster system. By commandeering more than half the South's produced goods for the military, the quartermaster general, in a drift toward socialism, appropriated hundreds of mills and controlled the flow of.